LITERASI KEUANGAN DAN PERAN PERGURUAN TINGGI DALAM MEMBENTUK KARAKTER CERDAS KEUANGAN MENUJU INDONESIA EMAS 2045: Financial Literacy and the Role of Higher Education in Shaping Financially Savvy Character Towards a Golden Indonesia 2045 - Hani Hatimatunnisani (JURNAL PENDIDIKAN, HUMANIORA, LINGUISTIK DAN SOSIAL (JAGADDHITA), 2026)
Financial literacy is an individual’s ability to understand and use various information and apply financial concepts for decision making. University has a strategic role in increasing financial literacy and forming intelligent character in financial management among student, which in the future will play a role in the movement of the Indonesian economy towards the goal of a Golden Indonesia 2045. This research aims to analyze the level of financial literacy of students and the role of university and its influence on the formation of financially intelligent character. Research was conducted quantitatively on 128 private university students in Bandung. The result show that financial literacy and the role of university have a positive and significant influence on the formation of financially intelligent character. Through education curriculum, training, developing a healthy financial culture, and a good financial literacy that is instilled in universities, it can certainly help in creating a young generation that is intelligent, independent, and responsible in financial management so that it can support the achievement of a Golden Indonesia 2045.